Professional Thinking and Types of Professionals - Gilmanov, S (KnE Life Sciences, 2018)
We believe that main parameters of professional thinking are: the conceptual development of professional reality (as a separate socio-cultural area of activities and relationships embodied in the objectives, actions, functions of profession) and the adequacy of planning and regulation of actions in professional situations. The parameters of the professional thinking specify types of professionals. We investigated the parameters of professional thinking and the types of professionals through analysis of speech (dialogues, descriptions of professional activities, etc.) of people of different professions (n = 224) based on the ideas of A. R. Luria: (1) ‘The real use of the word <...> is always the process of selecting the desired meaning from the pop-up alternatives, with the allocation of some actual system ties and inhibition of other systems of relations, not relevant to this problem’; (2) the meaning of the word depends on the specific task facing the subject and situation in which the word is used. The units of meaning were: understanding of structural and dynamic sides of the professional reality; way of substantiation actions in professional situations. The data allowed to determine three types of professionals. (1) ‘Expert’: there is a complete and profound reflection of professional reality in the speech combined with the exact description of planned actions. (2) ‘Inept maven’: understands the professional activity and its components, but may not accurately describe the actions. (3) ‘Empirical practician’: can describe the correct actions, but descriptions are based on experience and stereotypes. Keywords: professional speech, professional thinking, professional reality, types of professionals